Screening for Common Respiratory Diseases among Israeli Adolescents - Yaron Bar Dayan; Keren Elishkevits; Liav Goldstein; Avishay Goldberg; Michel Fichler; Nisim Ohana; Yehezkel Levi; Yosefa Bar Dayan (Canadian Respiratory Journal)
BACKGROUND: Respiratory diseases are responsible for a significant proportion of serious morbidity among adolescents. There are few reports on the prevalence of common respiratory disorders in this population. The previous studies focused on specific diseases and screened relatively small samples.